METODE TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PENGOLAHAN DATA - Maman Ahdiyat (Faktor Jurnal Ilmiah Kependidikan, 2014)
Abstract By using Methodology of peer tutoring is to increase the result of mathematics study on statistic at sixth grade of elementary school This research is aimed (1) To know the result of mathematics study on tutor methodology (2) To know empirical of the effected of peer tutoring to mathematics study result. The research has been using experiment. The hypothesis result found that, there is deferent between using of tutor and lecture methodology. Key words: Peer Tutoring, Lecture, Mathematics study result